Indikasi Going Concern Ditinjau dari Risk Manajemen Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (JHP17 (Jurnal Hasil Penelitian), 2017)
The results showed that from 25 manufacturing companies in 2015, 18 companies have aged receivables under 90 days this means the period of collection of fast receivables will not result in bad debts so that cash inflows to companies are not hampered then the company can be said going concern. Current Ratio 20 companies have a current ratio of more than 100% and Quick Ratio 14 companies more than 100% Â indicating that the company does not menglami liquidity in the sense that it can meet its short-term obligations in the long term with a large number it can be said going concern company. The sales growth of 23 companies by 2015 has decreased sales and 21 companies have decreased dividend so that operational cost efficiency should be increased. Manufacturing companies in 2012 until 2015 asset growth has increased that is offset by the growth of long-term debt is also experiencing an increase it can be said that the company going concern. Of the 25 manufacturing companies 2012 to 2015 have a profitability ratio measured by NPM, ROA and ROE average is positive so it can be said that the company going concern. The change of inflation in 2015 from 25 manufacturing companies decreased, and the rupiah exchange rate change to US $ in 2015 also decreased, so that the entrepreneurs have an interest in developing their business in macro sectors.Â Keywords: Going Concern, Risk Management, Open Manufacturing CompanyÂ